Association between functional polymorphisms of Foxp3 and Interleukin-21 genes with the occurrence of recurrent pregnancy loss in Gaza strip-Palestine - Jaber, Mohammed O.; Sharif, Fadel A. (International Journal of Research in Medical Sciences, 2017)
Background: This study was conducted in order to investigate the association between IL-21 (rs2055979 G/T and rs13143866 A/G) and Foxp3 (rs2232365 A/G and rs3761548 A/C) gene polymorphisms and recurrent pregnancy loss (RPL) in a group of Palestinian women residing in Gaza strip. Methods: A retrospective case-control study was carried out during the period (January to June, 2014). A total of 200 females, 100 RPL patients and 100 controls women without previous history of RPL, aged 20–35 years were included in the study. IL-21 rs13143866 A/G and Foxp3 rs2232365 A/G polymorphisms were analyzed by allele-specific PCR whereas, IL-21 rs2055979 G/T and Foxp3 rs3761548 A/C polymorphisms were investigated by PCR-RFLP. Results: No statistically significant difference existed between RPL cases and controls in terms of the allelic and genotypic distribution of IL-21 rs2055979 or rs13143866. On the other hand, the two Foxp3 gene polymorphisms showed statistically significant association with RPL: the rs2232365 A/G allele G and its homozygous genotype G/G and the rs3761548 A/C allele A and its A/A genotype were significantly higher in RPL group. Conclusions: Foxp3 rs2232365 A/G and rs3761548 A/C polymorphisms represent risk factors for RPL in Gaza strip women. IL-21 polymorphisms rs2055979 G/T and rs13143866 A/G however, do not pose tangible risk for RPL in our population. Study results should be confirmed on a larger sample.